Knowledge, attitude, and practice regarding the COVID-19 pandemic and its psychological impact on nursing students in Palestine - Rebhi Bsharat; Nawaf Amro; Hamdallah AbuKallid; Abdallah Alwawi (Journal of Preventive and Complementary Medicine)
Background: Understanding individuals' knowledge, attitudes, and practices concerning preventive measures for COVID-19 is crucial for controlling the disease's spread.Objectives:  This study aims to evaluate nursing students' knowledge, attitudes, and practices related to the pandemic while assessing its psychological impact on them to inform future interventions.Methods: A cross-sectional questionnaire-based study was conducted through an online survey in May 2020. All nursing students enrolled in nursing colleges across Palestinian universities were invited to participate.Results: Out of 740 nursing students, 420 responded, resulting in a response rate of 56.75%. The average knowledge score was 9 ± 2.364 (maximum possible score: 12). Notably, 68.1% of nursing students recognized COVID-19 as a significant health threat to their community during the early months of the pandemic. Additionally, 52.6% believed that the initial lockdown was essential for controlling the virus's spread. Encouragingly, 66.4% refrained from visiting crowded places during this period. Female nursing students demonstrated significantly higher knowledge scores compared to their male counterparts (p<0.001). Approximately two-thirds of the students adhered to recommended preventive strategies. However, 41.4% reported feeling nervous or anxious frequently during the pandemic.Conclusion: The findings indicate that nursing students possessed a solid understanding, positive attitudes, and appropriate practices regarding COVID-19 and its preventive measures. Nevertheless, the pandemic adversely affected the psychological well-being of many students during its initial months. Therefore, it is imperative to implement proactive psychological and social support services for students during current and future pandemics. Furthermore, addressing potential stressors associated with the transition to distance learning and assessment should be prioritized.